A STUDY ON THE ANTICANCER ACTIVITY OF ETHANOL EXTRACT OF ARISTOLOCHIA MOLLISSIMA HANCE ON OSTEOSARCOMA HOS CELLS - Yu, Yu; Bo, Zhao; Chao, He; Minghua, Zhang (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This paper mainly studied the extraction process of traditional Chinese medicine Aristolochia mollissima Hance (Aristolochiaceae) and the inhibitory effect of its extracts on osteosarcoma HOS cells. The extraction process included the ultrasonic extraction method, heat reflux method and decoction method to obtain three different extracts. MTT assay was used to test the effect of the extracts on proliferation of HOS cells, to compare the degree of inhibitory activity of three extracts, and to calculate cell survival rates. The results showed that among the three extracts obtained by the ultrasonic extraction method, heat reflux method and decoction method, the one obtained by ultrasonic extraction has the largest yield, but the extract obtained by heat reflux method has the strongest anticancer activity. Nevertheless, the three extracts all have a good inhibitory activity on the proliferation of osteosarcoma HOS cells.